Perceived School Climate and Chinese Adolescents' Suicidal Ideation and Suicide Attempts: The Mediating Role of Sleep Quality. (February 2016) - Li, Dongping; Bao, Zhenzhou; Li, Xian; Wang, Yanhui
ABSTRACT: BACKGROUND: School factors play important roles in adolescent suicide. However, little is known about how school climate is associated with adolescent suicide. This study examined the relationship between perceived school climate and adolescent suicidal ideation and suicide attempts, and whether these relations were explained by adolescent sleep quality. METHODS: A total of 1529 Chinese adolescents (mean age = 14.74 years; 52% boys) participated in the study. They provided self‐report data on control variables, perceived school climate, sleep quality, suicidal ideation, and suicide attempts. RESULTS: After controlling for sex, age, family structure, socioeconomic status, and parent‐adolescent attachment, we found that perceived school climate negatively predicted adolescent suicidal ideation (odds ratio [OR] = 0.66, p < .001) and suicide attempts (OR = 0.72, p < .001). Moreover, perceived school climate positively predicated adolescent sleep quality (β = 0.13, p < .001), which in turn, negatively predicted adolescent suicidal ideation (OR = 0.75, p < .001) and suicide attempts (OR = 0.76, p < .001). CONCLUSION: These findings, although cross‐sectional, indicate that perceived school climate plays an important role in adolescent suicidality. Moreover, the relation between perceived school climate and adolescent suicidality was largely mediated by adolescent sleep quality.